O sujeito e a emergência do cuidado de si em Foucault - Nunes, Michael Douglas de Almeida (2013)
This work aims to present a possibility to think the subject, from those that are considered the three phases of Michel Foucault. In the first phase, the Archaeology of Knowledge, there is an impossibility to conceptualize the man, because he is one with the world in the Age of Resemblance and represented as a subject of knowledge in the Age of Representation, which will ratify the disappearance of the modern subject in Modernity with the emergence of the human sciences. On the Genealogy of power this same subject is within mechanisms of power and modes of subjection that preclude to think a relationship between a man and a truth about himself, because this subject, who is subjugated, is immerse in the sphere of heteronomy. In the last phase, also called of the last Foucault, seeks to defend a statute for the real subject that it is not the modern subject anymore, nor the subject subjugated. Searching for a relationship between the new format of subject and a true possible, considering the modes of subjectivation, the concepts and practices developed by Greeks in Classic Greece, extended in a culture of the care of the self and the others, through the true discourse, the speaking freely, the parrhesia.